2020
DOI: 10.1111/jgh.15214
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic autoimmune diseases in primary biliary cholangitis: Prevalence and significance for clinical presentation and disease outcome

Abstract: Background and Aim: The prevalence and clinical significance of extrahepatic autoimmune diseases (EHAIDs) have not been evaluated in a large cohort of primary biliary cholangitis (PBC). Methods: The medical records of 1554 patients with PBC from 20 international centers were retrospectively reviewed. Development of decompensated cirrhosis (ascites, variceal bleeding, and/or hepatic encephalopathy) and hepatocellular carcinoma were considered clinical endpoints. Results: A total of 35 different EHAIDs were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
3
38
2
Order By: Relevance
“…These results were compatible with previous reports [8,11,13] but lower than those of the Italian group. Autoimmune thyroid disease was the most frequently observed, with a prevalence of 10% and 15%, [5,8,[11][12][13] which was similar to our results (20%). The differences mostly seen in the pattern of the EAD.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results were compatible with previous reports [8,11,13] but lower than those of the Italian group. Autoimmune thyroid disease was the most frequently observed, with a prevalence of 10% and 15%, [5,8,[11][12][13] which was similar to our results (20%). The differences mostly seen in the pattern of the EAD.…”
Section: Discussionsupporting
confidence: 93%
“…Among the EAD, autoimmune thyroid disease was most commonly encountered (20%), followed by Sjogren syndrome (12%). This finding is compatible with previous studies, [5,7,8,[11][12][13] which reported a close association between EAD and ALD, and autoimmune thyroid disease was most frequently encountered. Because the association between AIH and EAD is well known, these results indicate that high frequency of concomitant EAD was also seen in patients with OS and PBC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prevalence of AIHA in PBC patients is variable. In a large international cohort of 1554 patients with PBC, AIHA was diagnosed in 0.2% [ 50 ]. In a retrospective study of 71 patients with AIH/PBC overlap syndrome, 43.6% had an extrahepatic autoimmune manifestation and 1.4% developed AIHA [ 51 ].…”
Section: Hepatic and Gastrointestinal Disorders Predisposing To Aumentioning
confidence: 99%